2007
DOI: 10.1177/0743558406295783
|View full text |Cite
|
Sign up to set email alerts
|

“I Hated Her Guts!”: Emerging Adults’ Recollections of the Formation, Maintenance, and Termination of Antipathetic Relationships During High School

Noel A. Card

Abstract: Antipathetic relationships have received little empirical attention. This study examines these relationships by eliciting college students' descriptions of the formation, patterns of interpersonal behaviors, and termination of antipathetic relationships during high school. Factors that differentiate inimical from other antipathetic relationships are also investigated. The Interview of Friendship and Antipathetic Experiences, a semistructured retrospective interview of high school relationships, was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…As reported in Card (2007), results indicated that antipathetic relationships are quite common: 75% of participants identified a particular peer that they disliked or considered an enemy during high school. Of the 60 participants who reported experiencing an antipathetic relationship in high school, 43% were formerly friends.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…As reported in Card (2007), results indicated that antipathetic relationships are quite common: 75% of participants identified a particular peer that they disliked or considered an enemy during high school. Of the 60 participants who reported experiencing an antipathetic relationship in high school, 43% were formerly friends.…”
Section: Resultsmentioning
confidence: 65%
“…Antipathetic relationships have been speculated to form for a wide variety of reasons, such as competition for limited resources, personality clashes, and broken friendships (Abecassis, 2003;Wiseman & Duck, 1995). There is also evidence that these relationships often contain conflict during the formation, and aggression and avoidance during their course (Card, 2007). The current study extends these possibilities by considering the unique aspects of the formation and course of antipathetic relationships that emerge from broken friendships.…”
mentioning
confidence: 87%
“…In addition to revenge, the context of animosity is likely to foster avoidance motivation. For instance, college students report that avoidance is one of the most common ways of dealing with a disliked peer (Card, 2007).…”
Section: Role Of Relationship Contextmentioning
confidence: 99%
“…In contrast to friendships, however, these are relationships in which each individual dislikes the other. The exact nature of this dislike varies across conceptualizations and the few studies that have examined these relationships, ranging from mere aversion (e.g., someone the child does not like to work or play with) to more intense disliking (e.g., enmity, hatred; see Abecassis, 2003; Hartup, 2003), and further research examining the meaningful distinctions that individuals make among their antipathetic relationships is needed (see Card, 2007). Nevertheless, it has been argued that (at least some) antipathetic relationships are marked by an intense, personal form of rejection with distinct patterns of interactions and unique developmental risks beyond those associated with group‐level (unilateral) rejection (see Abecassis, Hartup, Haselager, Scholte, & Van Lieshout, 2002; Hartup & Abecassis, 2002; Schwartz, Hopmeyer Gorman, Toblin, & Abouezzedine, 2003; cf.…”
mentioning
confidence: 99%